Dialectiques hydrosociales à l’épreuve. Décrypter la dimension politique d’objets techniques utilisés pour l’irrigation au Népal - Romain Valadaud; Olivia Aubriot (Développement Durable et Territoires)
The hydrosocial cycle is a key concept to overcome the nature / society dichotomy. This article seeks to clarify its analytical and operational scope through the study of a Nepalese irrigation system. The combination of a sociotechnical approach, based on the analysis of technical objects, and of a critical realist approach, underlining the importance of the relationship between structure and agency, helps to bring out the political dimensions of these objects. We therefore show how canals or plastic tubes are integral parts of the power play within irrigation associations and beyond. It is by analyzing the changes in their (practical and political) use that we understand their role in the reproduction of the clientelist social structure of rural Nepal.